Mechano-tunable chiral metasurfaces via colloidal assembly - Probst, Patrick T.; Mayer, Martin; Gupta, Vaibhav; Steiner, Anja Maria; Zhou, Ziwei; Auernhammer, Gunter K.; Koenig, Tobias A. F.; Fery, Andreas (Nature Materials, 2021)
Dynamic control of circular polarization in chiral metasurfaces is being used in many photonic applications. However, simple fabrication routes to create chiral materials with considerable and fully tunable chiroptical responses at visible and near-infrared wavelengths are scarce. Here, we describe a scalable bottom-up approach to construct cross-stacked nanoparticle chain arrays that have a circular dichroism of up to 11 degrees. Due to their layered design, the strong superchiral fields of the inter-layer region are accessible to chiral analytes, resulting in a tenfold enhanced sensitivity in a chiral sensing proof-of-concept experiment. In situ restacking and local mechanical compression enables full control over the entire set of circular dichroism characteristics, namely sign, magnitude and spectral position. Strain-induced reconfiguration opens up an intriguing route towards actively controlled pixel arrays using local deformation, which fosters continuous polarization engineering and multi-channel detection.
CRIS-Team WoS Importer:2021-05-21